Drug Delivery - Schäfer-Korting, Monika; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
In the view of most experts pharmacology is on drugs, targets, and actions. In the context the drug as a rule is seen as an active pharmaceutical ingredient and not as a complex mixture of chemical entities of a well defined structure. Today, we are becoming more and more aware of the fact that delivery of the active compound to the target site is a key. The present volume gives a topical overview on various modern approaches to drug targeting covering today’s options for specific carrier systems allowing successful drug treatment at various sites of the body difficult to address and allowing to increase the benefit-risk-ratio to the optimum possible.
Fundamentals -- Passive and Active Drug Targeting: Drug Delivery to Tumors as an Example -- Nanoparticle Technologies for Cancer Therapy -- Biosensing and Drug Delivery at the Microscale -- Devices -- Lipid Nanoparticles: Effect on Bioavailability and Pharmacokinetic Changes -- Viral Vectors for Gene Transfer: Current Status of Gene Therapeutics -- Pulmonary Drug Delivery: Medicines for Inhalation -- Needle-Free Vaccine Injection -- Pharmaceutically Used Polymers: Principles, Structures, and Applications of Pharmaceutical Delivery Systems -- Mucoadhesive Drug Delivery Systems -- Intrauterine Drug Delivery for Contraception and Gynaecological Treatment: Novel Approaches -- Drug-Eluting Medical Implants -- Clinical and Preclinical Application of Therapeutics for Systemic Use -- Improving Oral Delivery -- Transdermal Drug Delivery -- Targeting the Brain – Surmounting or Bypassing the Blood–Brain Barrier -- Clinical and Preclinical Application of Therapeutics for Topical Use -- Carriers in the Topical Treatment of Skin Disease -- Medical Devices for the Treatment of Eye Diseases -- Erratum to: Biosensing and Drug Delivery at the Microscale.
Keywords: Pharmacology; Pharmaceutical technology; Oncology .; Dermatology; Neurology .; Pharmacology/Toxicology.; Pharmaceutical Sciences/Technology.; Oncology; Dermatology; Neurology